PRAKTIK DOMINASI TOKOH ANTAGONIS MELALUI KEKERASAN SIMBOLIK DALAM FILM BETTER DAYS《少年的你》 - Muhammad Farhan Masrur (Unit Pengembangan Bahasa UIN Sayyid Ali Rahmatullah Tulungagung, 2022)
When language is used in communication events, there also as an ideological distiction and a desire to dominate each other among its users. Because language is never separated from ideological motives, including domination motives. Domination occurs due to the existence of a strong group as the dominating party and a weak group as the dominated party with language as an instrument to achieve it. Symbolic violence marked by language forms that represent language crimes is a realization of the practice of domination. Through symbolic violence, the dominant party imposes its ideological influence on the dominant group. The practice of domination through symbolic violence can be found in the dialogue text of the antagonist in the film Better Days《少年的你》by Derek Tsang which is used as a data source. The patterned language forms used by the antagonist to attack the main character are used as data. After the data is identified and classified, it is analyzed through a qualitative approach using the concept of Bourdieu's theory of symbolic violence. The results of the analysis are presented through a descriptive method to obtain a detailed and concrete picture of the practice of domination of antagonist characters through symbolic violence. The results of the analysis show that symbolic violence, which represents the practice of domination, is realized through forms of language that have functioned as the language of punishment, the language of intimidation, the language of prohibition, the language of accusation, the language of insults, and language of command. Cultural capital (attitudes and lifestyles) is the most dominant capital that represents the attitudes and behavior of antagonists to produce and reproduce texts to legitimize their domination. Based on the frequency of occurrence, forbidden language is the most productive form of language, and accusation language is the language form with the least frequency of occurrence.